2011
DOI: 10.1111/j.1365-2621.2011.02859.x
|View full text |Cite
|
Sign up to set email alerts
|

Portuguese bee pollen: palynological study, nutritional and microbiological evaluation

Abstract: Bee pollen is one of the richest and purest natural foods, used in the folk medicine, clinical practices, and food and pharmaceutical industries. This work aims to characterise, for the first time in Portugal, the palynological origin, nutritional value and microbiological safety of this beehive product. It identified ten botanical families, and the more frequent were Boraginaceae and Ericaceae. We have evaluated the water content, a w , pH, reducing sugars, ash, carbohydrate, proteins, lipids, fatty acids and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
82
2
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 24 publications
(34 reference statements)
15
82
2
10
Order By: Relevance
“…The values of physicochemical were similar to the reports available in the literature (Arruda et al, 2013;Campos et al, 2008Campos et al, , 2016Estevinho et al, 2012).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The values of physicochemical were similar to the reports available in the literature (Arruda et al, 2013;Campos et al, 2008Campos et al, , 2016Estevinho et al, 2012).…”
Section: Resultssupporting
confidence: 90%
“…Bee pollen has a variable chemical composition, being the major compounds proteins, carbohydrates, sugar, lipids, fibres, vitamins and minerals (Arruda, Pereira, de Freitas, Barth, & de AlmeidaMuradian, 2013;Campos et al, 2016;Estevinho, Rodrigues, Pereira, & Feás, 2012;Yang et al, 2013) and depends of the floral origin (Morais, Moreira, Feás, & Estevinho, 2011). According Campos, Olena, and Anjos (2016) bee pollen contain all the essential amino acids needed for the human organism.…”
Section: Introductionmentioning
confidence: 99%
“…Even bee pollen from the same plant species harvested in distinct areas will contain differences in their chemical quality (Denisow;Denisow-Pietrzyk, 2016), and extensive research is required before bee pollen can be used in therapy, although it can unequivocally be recommended as a valuable dietary supplement. After studying bee pollen from Portugal, Morais et al (2011) and Estevinho et al (2012) reported that one of the fundamental aspects for the beneficial qualities of bee pollen is its botanical and geographical declaration of origin. Generic pollen composition data were previously considered sufficient, but now, the usefulness of specific data is increasingly being acknowledged since several studies indicate appreciable differences among the compositions of bee pollen from variable regions.…”
Section: Introductionmentioning
confidence: 99%
“…Os valores obtidos por Estevinho et al, (2012), Nogueira et al, (2012) e Feas et al, (2012), em amostras desidratadas de pólen apícola orgâncio e pólen apícola comercial portugueses foram inferiores aos determinados neste estudo. Do ponto de vista microbiólogico os valores de bolores e leveduras estão relacionados com as condições ambientais, e são indicativos de uma gestão adequada ou ineficiente dos apiários (NOGUEIRA et al, 2012).…”
Section: Dados De Recuperação (%)unclassified
“…Os aeróbios mesófilos estiveram presentes em 56% das amostras, Os indicadores de segurança (esporos de clostrídios sulfito redutores) estiveram ausentes em todas as amostras analisadas, assim como observado por Estevinho et al, (2012), Nogueira et al, (2012), Feas et al, (2012) e Coronel, et al, (2004.…”
Section: Dados De Recuperação (%)unclassified